Gastronomy tourism: an opportunity for local development in Catalonia? A stakeholder analysis - Maria Del Pilar Leal Londo\~no (European Regional Science Association (ERSA), 2011)
The development of tourism and particularly public administration have had to adapt to new trends and the demands of the tourist market (Fayos-Solá, 2004) especially in Spain, thus generating some of the most remarkable and structural changes which constitute the emergence of new touristic dynamics (Lopez Palomeque and X. Font, 2010). The Catalan territory, which has participated in those dynamics where wine tourism becomes an alternative product of the diversification of touristic offerings, traditionally focused on sun-and-beach not only in this region but also in the whole of Spain. To revitalize the touristic offer historically focused on sun and Beach tourism, the Catalan government , bet for the gastronomic tourism through the creation of the strategies as the Gastronomic Club in 2001 or the Gastroteca in 2006; which link different stakeholders not only publics but also privates (travel agencies, universities, private foundation, NGO, producers, etc) interested in gastronomy, responding to this phenomenon that is increasing around the world and specially in Catalonia thanks to important figures like one of the most well known chefs around the world which is Ferran Adrià. Catalonia as a region is particularly varied, no only because it's characteristics biogeographically but also for its touristic resources, generating in this territory the production of a set of "micro territories" which are constantly looking for authenticity and differentiation from highly competitive tourism brands such as the city of Barcelona. This paper analyzes the advantages and disadvantages which arise this new touristic phenomenon in Catalonia and its relationship with the local development in different scales; through the perceptions and actions carried out for the stakeholders involved in this strategy. To achieve this, was taken the reflexions and the relationships that keep between them, 12 personalities from the public and private sector and the academy. Were applied semi structured interviews and them perceptions were systematized and analyzed using SWOT (Strengths, Weaknesses, Opportunities, Threats) methodology as the primary tool. This methodology, examines this phenomenon in Catalonia and its possibilities as a generator of local and regional development.
Keywords: 330; Gastronomic tourism; local development; stakeholders; Catalonia